Belinda of the Red Cross - Hamilton, Robert W.; Scott, A. O. (Arthur Orange), 1882?-1946 (Salt Lake City, UT : Project Gutenberg, 2024)
"Belinda of the Red Cross" by Robert W. Hamilton is a novel written in the early 20th century. The story follows Belinda Melnotte, a compassionate nurse, as she navigates her complex feelings for her patient, an aviator named Frank Sanderson. As World War I unfolds, she grapples with her desire to help others through Red Cross service, even as personal relationships and the chaos of war challenge her convictions. At the start of the novel, readers are introduced to Belinda in a hospital setting, where she assists in the treatment of Sandy Sanderson, a young and reckless aviator who has been injured in a flying accident. The banter between Belinda and her fellow nurse, Sue, reveals the camaraderie among the nurses as they care for patients under harrowing circumstances. Belinda's professional demeanor contrasts sharply with her emerging feelings for Sandy as he recovers from his injuries. The tension escalates when hints of his complicated personal life begin to surface, leaving Belinda at a crossroads between her growing affection for him and her steadfast commitment to her nursing career and the suffering soldiers of the war. (This is an automatically generated summary.)
Robert W. Hamilton was a pseudonym used by the Stratemeyer Syndicate. Some sources credit Edward Stratemeyer as the author of this work, for example: https://catalog.hathitrust.org/Record/100587982
Release date is 2024-10-12
Jamie Brydone-Jack, Mary Meehan and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: World War, 1914-1918 -- Fiction; War stories; Love stories; Nurses -- Fiction; Air pilots, Military -- Fiction